INOVASI PELAYANAN PUBLIK DI ERA NEW NORMAL - Sa'ban, L.M. Azhar (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Public services that have been carried out by direct interaction must be limited and even have to switch to online services. In this new normal era, public services should not decrease in quality. The Covid-19 pandemic should not hinder and be the reason for limitations in public services. The purpose of this study is to find out how the Department of Population and Civil Registration of Baubau City innovates in public services in the New Normal Era. The method used in this research is descriptive qualitative. Data collection techniques used are interviews, and documentation. The results of the study are changes in public services carried out in the Department of Population and Civil Registration of Baubau City in the New Normal Era. In the new normal era, the ASN of the Population and Civil Registration Office of the City of Baubau made adjustments to the work system, such as counter officers being required to wear masks and be provided with hand sanitizers as well as performing population administration services (Admindu) with an online system, the Covid-19 condition resulted in many electronic-based public service innovations. , so that it is necessary to strengthen quality and innovative ASN human resources, as well as support infrastructure development.Keywords: Public Service, State Civil Apparatus, New Normal